Fiscal Policy in Iraq after the Deterioration of Oil Prices: Coping Strategies and Alternatives - Zayer, Ahmed Abd Rwdhan (Research Parks Publishers, 2025)
Wealthy Iraq is entirely reliant on oil revenues, which makes the economy highly exposed to dips in international oil values. Iraq's fiscal space has been increasingly constrained by the collapse in oil prices that has led to a series of successive budget deficits, increasing public debt and economic instability. This paper examines the fiscal policy measures that the Iraqi government has implemented in reaction to falling oil prices, such as austerity, higher borrowing, and currency depreciation. It assesses the success of these strategies and notes other approaches to achieving long-term fiscal sustainability. Diversifying the economy, reforming the tax system, and enhancing public expenditure management are key objectives for reducing Iraq's dependence on oil revenues, according to the study. Such steps will help Iraq develop a more independent economy that can resist shocks from oil prices in the future and instead realise a sustainably developing economy.